Behavioral Regulation Sport Questionnaire: Gender and Sport Invariance in Portuguese Athletes - Monteiro, Diogo (2019)
This study aimed to analyze measurement invariance of the Behavioral Regulation Sports Questionnaire (BRSQ) across the gender and four different sports. In addition, we examined nomological validity via basic psychological needs satisfaction. Participants totaled 1,812 Portuguese athletes (1,220 males and 592 females; aged 15–59 years, Mage ¼ 17.72, SD ¼ 5.51) from football (n ¼ 596), basketball (n ¼ 273), swimming (n ¼ 800), and parasport (n ¼ 143). The BRSQ measurement model was invariant across the gender and these four sports. The scale confirmed nomological validity in that satisfaction of the basic psychological needs positively predicted autonomous forms of motivation and negatively predicted more controlled motivation and amotivation as suggested by self-determination theory. In light of this evidence for BRSQ construct validity, composite reliability, nomological validity, and invariance across the gender and four different sports, this scale is a useful tool for the coaches of the aforementioned sports in their efforts to evaluate their athletes’ motivation.